2018
DOI: 10.5483/bmbrep.2018.51.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance of bladder cancer cells through activation of ABCG2 by FOXM1

Abstract: Recurrence is a serious problem in patients with bladder cancer. The hypothesis for recurrence was that the proliferation of drug-resistant cells was reported, and this study focused on drug resistance due to drug efflux. Previous studies have identified FOXM1 as the key gene for recurrence. We found that FOXM1 inhibition decreased drug efflux activity and increased sensitivity to Doxorubicin. Therefore, we examined whether the expression of ABC transporter gene related to drug efflux is regulated by FOXM1. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 30 publications
5
35
0
Order By: Relevance
“…For example, JNK contributes to the resistance of stem‐like glioblastoma cells to temozolomide. Moreover, O 6 ‐methylguanine DNA methyltransferase (MGMT) seems to be an important mediator in this context, since JNK activation induces MGMT expression; when JNK activity is inhibited, MGMT expression and temozolomide resistance decrease . Cisplatin is a chemotherapeutic drug used widely for the treatment of human cancers.…”
Section: Jnk Signaling Plays a Role In Cancer Chemoresistancementioning
confidence: 99%
See 3 more Smart Citations
“…For example, JNK contributes to the resistance of stem‐like glioblastoma cells to temozolomide. Moreover, O 6 ‐methylguanine DNA methyltransferase (MGMT) seems to be an important mediator in this context, since JNK activation induces MGMT expression; when JNK activity is inhibited, MGMT expression and temozolomide resistance decrease . Cisplatin is a chemotherapeutic drug used widely for the treatment of human cancers.…”
Section: Jnk Signaling Plays a Role In Cancer Chemoresistancementioning
confidence: 99%
“…JNK inhibition reduced the PTMA protein stability and sensitized HCC cells to cisplatin. ATP‐binding cassette subfamily G member 2 (ABCG2), a half‐transporter belonging to the G subfamily of ATP‐binding cassette transporter (ABC) transporter genes, plays an important role in multidrug resistance . Zhu et al, showed that JNK1 signaling is involved in multidrug resistance of colon cancer cells.…”
Section: Jnk Signaling Plays a Role In Cancer Chemoresistancementioning
confidence: 99%
See 2 more Smart Citations
“…Many chemotherapeutics are known to be ABCG2 substrates, such as mitoxantrone, methotrexate, doxorubicin, diflomotecan, topotecan, and SN-38 (an active metabolite of irinotecan; Erdei et al, 2018;Hira & Terada, 2018). ABCG2 activity is linked to chemoresistance in various cancers, including ovarian cancer , pancreatic cancer (Stern et al, 2018), lung (Xie et al, 2018) and bladder cancer (Roh et al, 2018). CCN family member 2 (CCN2) (also known as connective tissue growth factor [CTGF]) acts as a multifunctional signaling modulator in various biologic or pathologic processes (Luft, 2008).…”
Section: Introductionmentioning
confidence: 99%